The Study of the Cytotoxicity, Proliferative and Microbiological Activity of the Medicated Chewing Gum with Ascorbic Acid and Lysozyme Hydrochloride Using Different Culture of Cells - Yuliia Maslii; Liudmyla Garmanchuk; Olena Ruban; Taisa Dovbynchuk; Nataliia Herbina; Giedre Kasparaviciene; Jurga Bernatoniene (MDPI AG, 2023)
Medicated chewing gum with lysozyme hydrochloride and ascorbic acid as active pharmaceutical ingredients was developed for application in dentistry. The aim of this research was to study the cytotoxicity, proliferative, and microbiological activities of the active ingredients in different types of cell cultures. The preclinical study of active pharmaceutical ingredients and their combinations was carried out using culture lines such as HepG2 (human hepatocarcinoma cells), Hek293 (human embryonic kidney cells), and MAEC (mouse aortic endothelial cells). MTT assays were used to analyse cytotoxicity and proliferative activity, while the state of antioxidant protection was assessed by the content of sulfhydryl groups and catalase activity. The determination of lipid peroxidation products was based on the level of TBA-active products. As a microbiological model for studying the effect of the developed dental medicine on the ability of the oral cavity microorganisms to form biofilms, the following strains were used: Streptococcus mutans, Staphylococcus aureus, Staphylococcus epidermidis, Lactobacillus plantarum, and Candida albicans. The optical density of the formed biofilm was evaluated by the intensity of the experimental sample's colour on a StatFax 303 Plus photometer at a wavelength of 630 nm. The combination of ascorbic acid and lysozyme hydrochloride in the established concentrations (20 mg and 10 mg per 1 gum, respectively) resulted in a slight stimulation of cell proliferation without any toxic effects and increased antioxidant protection, preventing the development of oxidative stress. It was found that, in contrast to the separately used active substances, the combination of lysozyme hydrochloride and ascorbic acid inhibits the biofilm formation of all studied microorganisms and shows the ability to destroy diurnal biofilms of L. plantarum and fungi of the genus Candida, indicating potentiation and summation of the active pharmaceutical ingredients' composition effects in the developed dental medicine. Due to the observed positive pharmacological and microbiological action, the combination of lysozyme hydrochloride and ascorbic acid in the medicated chewing gum serves as a promising tool for the prevention and treatment of infectious and inflammatory diseases of the periodontium and mucous membranes and the prevention of caries.